Reflective centers of module categories and quantum K-matrices - Robert Laugwitz; Chelsea Walton; Milen Yakimov (Forum of Mathematics, Sigma)
Our work is motivated by obtaining solutions to the quantum reflection equation (qRE) by categorical methods. To start, given a braided monoidal category